IAEA Additional Protocol: Prospects and Challenges for Pakistan - Mr. Majid Mahmood; Ms. Hajira Asaf Khan (CISS Insight Journal, 2016)
Pakistan aspires to be mainstreamed in the global nuclear order because it believes it has the requisite credentials. This particular Pakistani assertion grew stronger after US led efforts succeeded in granting India the waiver by the Nuclear Suppliers group (NSG) in 2008. The exemption was followed by India specific safeguards agreement with the International Atomic Energy Agency (IAEA) and the conclusion of various civil nuclear agreements between India and the major nuclear powers. The legitimization of nuclear trade with India resulted in its coming out of the isolation it has been facing at the international level and symbolizes its recognition as a nuclear power in the global nuclear order. Concerned at the country-specific waiver given to India, Pakistan has maintained that there should be criteria based approach for civil nuclear agreements with states outside the Treaty on Non-Proliferation of Nuclear Weapons (NPT) and no country should be discriminated against on political grounds. According to a recent National Command Authority (NCA) statement “NCA noted with satisfaction that Pakistan has the requisite credentials that entitle it to become part of all multi-lateral export control regimes, including the Nuclear Suppliers Group, for which Pakistan seeks adoption of a non-discriminatory approach.”